INCREASING (DEVELOPMENT) PROCESS'S CAPABILITY: IMPROVING SYSTEM'S IMMUNITY - Romans Djakons; Vsevolod Karayev; Rostislav Kopitov (Izdevnieciba "Baltija Publishing", 2021)
This approach is oriented to the identification of the weak links in the organization, which are allowing the improvement of the management system. Its essence is expressed by the knowledge of the means of identification of destructive forces, which do not only cause mismatching, but also introduce uncertainty, experience external influences and progress significantly. Such knowledge is accumulated by the effect of constant monitoring of the system, which is ensuring an increase in its performance. It also ensures the prevention of premature destructions of the organization, which does not allow it to acquire an unnatural state, by causing a real illness, which often leads to death. As a result, the implementation of the measures that contribute to such warnings productively affects the performance of the system and leads to a decrease in losses. Taking into account that the requirements for continuous monitoring of forces that are destroying the organization and their consequences are not consistent with the rules of the developers regarding the search for weak links in the smoothly running version of the system, the problem of the research was expressed in the following formulation: "It is impossible to make objective conclusions about the state of the organization in the absence of means for setting the objectively specified standards". The object of the research is characterized by the means of detection of the weak link in the system. Such means ensure the timely identification of the hidden reasons for the failure in its stable functioning. Thus, the degree of the expert's skill is manifested, which makes it possible to set limit to the accumulation of the spread of false knowledge by means of a full-scale three-level assessment of the current position before and after the localization of the place of failure in the stable functioning of the organization. As a practical result, it is worth noting that the measures taken to ensure reproducibility ensure the effectiveness of a full-scale assessment of the state of the organization. Moreover, their focus on provision of the integrity of the process includes a sequence of the interconnected tools that make it possible to move from long-term management within the framework of the cost pentagram to the implementation of a medium-term scenario as part of weighted sets of attributes, which were considered by taking into account the identified groups of critically influencing parameters that identify the degree of impact on the system of such subtle signals. The novelty of the proposed approach lies in the application of the technique of operational definitions that are supplemented by the mechanisms of the production of meaning, makes it possible to issue expert opinions on the current state of the organization within the framework of the continuous monitoring of the sustainable growth of the organization's potential.